Багатоваріантність форм власності та схем управління будинком в умовах України - Саркісова, К. М. (Ways to Improve Construction Efficiency, 2014)
Тhe rapid transformation of forms of the ownership and management of housing in Ukraine is considered beginning from state ownership of multiflat housing stock and till the private ownership of individual apartments. Hence the appeared discrepancy between subjects of ownership and objects of facilities management as integrated technical systems and property portfolios is demonstrated. The control schemes proposed by the standards documents of co-owners apartment buildings maintenance and operation are studied. In addition the effectiveness of the re-privatization or personalization of significant part of the multiflat housing stock, centralizing of building management functions, inviting of professional municipal and private companies to housing stock management using new methodology is based.